Condition assessment of reinforced concrete : bridge structure - M. Saeed, Aseel Abdulhaleem (2019)
The deterioration of concrete structures in the last few decades demands for effective methods for condition evaluation and maintenance. Currently, assessing the performance and safety of reinforced concrete (RC) structures relies on routine-based visual inspection (VI). However, there are other non-destructive test (NDT) techniques that can provide a more accurate assessment of the structures. Thus in this study, a pedestrian bridge located in Jalan Tun Abdul Razak, Johor Bahru is chosen as a case study, and has both VI and NDT techniques used for assessment. The main objective of this research is to determine the condition of bridge structural components and investigate its level of defect and deterioration using non-destructive tests. The methodologies involved are visual inspection and NDT techniques include the rebound hammer, cover meter, ultrasonic pulse velocity (UPV) and resistivity test. The methodology approach follows a condition assessment framework that was developed by previous literature with some modification. The framework when implemented with the best selection of NDT techniques helps in determine the level of defect and deterioration of the bridge structural components and next recommendation regarding the condition of the bridge. The involved bridge structural components includes column, deck, wall and staircase. Findings from the visual inspection shows that there were many defects and deteriorations found at the bridge structural components which includes crack, spalling, delamination and rusting. Further, NDT techniques that were carried out at the selected bridge structural component shows that some of the components exhibited moderate risk of corrosion and fair concrete surface quality. In general, further maintenance is needed specifically to some critical structural components of the bridge. Therefore, this research project concluded that visual inspection assisted with correct NDT techniques will help to investigate better current condition of bridge structural components. This will assist the stakeholders to take action immediately to the components with deteriorated conditions.